Exploring the impact of colostrum supplementation on athletes: a comprehensive analysis of clinical trials and diverse properties - Yalçıntaş, Yalçın Mert; Baydemir, Barış; Duman, Hatice; Eker, Furkan; Bayraktar Biçen, Ayşe; Ertürk, Melih; Karav, Sercan (Frontiers in Immunology, 2024)
Colostrum, an invaluable food produced by mammals during the postnatal period, contains important bioactive components. It is a valuable therapeutic substance that can be used to treat a variety of disorders, in addition to its primary function of providing passive immunity to newborns. Undoubtedly, a strong dedication to intense effort and demanding training schedules is necessary to succeed in today's sports environment. Peak physical fitness, strategic skill development, and mental toughness are highly valued in the environments in which athletes compete. However, the inherent difficulties brought about by athletes' intense schedules are matched with the demanding character of modern sports. The intensity of athletic activity frequently provides little time for sufficient relaxation, nutritional preparation, and overall recovery, which can contribute to mental and physical tiredness. Athletes need to develop all-encompassing strategies to overcome these obstacles. These strategies should prioritize self-care and recovery in addition to maximizing training efficiency. The bioactive components of colostrum bring forth various therapeutic effects against the challenges experienced by athletes; including diarrhea, upper respiratory tract infections, muscle injuries, intestinal disorders, etc. This review examined the different therapeutic effects of the bioactive components of colostrum on athletes, the effect of the use of colostrum as a whole on the performance of athletes, and the clinical research conducted in this field.While the majority of studies report positive effects of colostrum, further research is needed.